HERES, a lncRNA that regulates canonical and noncanonical Wnt signaling pathways via interaction with EZH2 - You, Bo-Hyun (Proc Natl Acad Sci U S A, 2019)
Wnt signaling through both canonical and noncanonical pathways plays a core role in development. Dysregulation of these pathways often causes cancer development and progression. Although the pathways independently contribute to the core processes, a regulatory molecule that commonly activates both of them has not yet been reported. Here, we describe a long noncoding RNA (lncRNA), HERES, that epigenetically regulates both canonical and noncanonical Wnt signaling pathways in esophageal squamous cell carcinoma (ESCC). For this study, we performed RNA-seq analysis on Korean ESCC patients and validated these results on a larger ESCC cohort to identify lncRNAs commonly dysregulated in ESCCs. Six of the dysregulated lncRNAs were significantly associated with the clinical outcomes of ESCC patients and defined 4 ESCC subclasses with different prognoses. HERES reduction repressed cell proliferation, migration, invasion, and colony formation in ESCC cell lines and tumor growth in xenograft models. HERES appears to be a transacting factor that regulates CACNA2D3, SFRP2, and CXXC4 simultaneously to activate Wnt signaling pathways through an interaction with EZH2 via its G-quadruple structure-like motif. Our results suggest that HERES holds substantial potential as a therapeutic target for ESCC and probably other cancers caused by defects in Wnt signaling pathways.